IMPLEMENTASI NILAI - NILAI KETUHANAN YANG MAHA ESA SEBAGAI DASAR PENDIDIKAN ANTI KORUPSI - Wiyono, Subelo (2014)
Indonesian nation have already owned religious values long before the proclamation of August 17 in 1945. In the history, Indonesian kept their own beliefs and made them as part of the character of Indonesian nation until Pancasila was appointed as the basis state. In formulating the basis for the country, Indonesian kept the value in the divinity of God which has rooted in Indonesian society life. Education becomes the focus of the nation durability in encountering the dangers which might bring the destructions. The education for anti-corruption is expected to give solution of the problems through bringing back to the root of Indonesian culture, called the value of divinity. This research tried to analyze the divinity value attached in Fakfak society which is presented in the following research questions: (1) how is the teaching learning system in Madrasah Tsanawiyah in Fakfak in order to build the students' character? (2) What kinds of divinity values taught by the teachers in Madrasah Tsanawiyah? (3) How are the teachers' comprehensions in the Madrasah Tsanawiyah towards the corruption which is against the divinity value? (4) How are the values comprehended by the students, especially in applying the divinity value in the teaching learning process (5) How are the students' understandings towards the value of building students' character, especially about corruption value?. Thus, this research uses The Four Stages System of Religion by Immanuel Kant as the grand theory. This qualitative approach using descriptive method was used in this research. Madrasah Tsanawiyah Muhammadiyah Fakfak and Madrasah Tsanawiyah Negeri Fakfak were chosen as the sites of the research. The result shows that (1) the divinity value is the method in building students' character, (2) The development of divinity value is in accordance with the first principle of Pancasila "Ketuhanan yang Maha Esa", (3) The teachers in Madrasah Tsanawiyah assured that corruption is against the religious values, (4) the divinity value is the value comprehended by the students (5) The students in Madrasah Tsanawiyah have already been formed the character such as divinity values and understood the anti-corruption values. Keywords: Pancasila, Divinity Value, Education, Anti-Corruption. Nilai-nilai religius sudah dimiliki bangsa Indonesia jauh sebelum Proklamasi 17 Agustus 1945. Dalam sejarah perjuangannya bangsa Indonesia tidak melepaskan keyakinan yang ada pada dirinya dan menjadikannya sebagai bagian dari karakter bangsa Indonesia. Hingga sampai pada puncak perjuang bangsa dimana akhirnya Pancasila ditetapkan sebagai dasar negara. Dalam merumuskan dasar negaranya Indonesia tidak melepaskan dari nilai Ketuhanan yang sudah mengakar dalam kehidupan masyarakat Indonesia. Pendidikan menjadi tumpuan harapan bagi daya tahan bangsa menghadapi bahaya yang hampir-hampir membawa kepada jurang kehancuran. Pendidikan Anti Korupsi diharapkan mampu memberikan solusi hingga mencapai akar persoalan. Pendidikan yang ingin dicapai adalah dengan mengembalikan ke dalam akar budaya masyarakat Indonesia yang berdasar nilai Ketuhanan. Penelitian ini akan mencoba untuk menganalis nilai-nilai Ketuhanan yang melekat pada masyarakat Fakfak. Secara garis besar permasalahan yang dikaji dalam penelitian ini adalah: (1) Bagaimana sistem pembelajaran di lingkungan Madrasah Tsanawiyah di Fakfak dalam membina karakter siswanya ? (2) Nilai-nilai Ketuhanan seperti apa yang diajarkan di lingkungan Madrasah Tsanawiyah ? (3) Bagaimana pemahaman tenaga pengajar di Madrasah Tsanawiyah tersebut terhadap tindakan korupsi yang bertentangan dengan nilai Ketuhanan? (4) Bagaimana nilai-nilai yang dipahami oleh siswa Madrasah Tsanawiyah, terutama penerapan nilai Ketuhanan selama kegiatan proses belajar mengajar ? (5) Bagaimana pemahaman siswa terhadap nilai-nilai dalam pembentukan karakter siswa, terutama pemahaman nilai anti korupsi ? Grand theory dalam penelitian ini adalah The Four Stages System of Religion menurut Immanuel Kant. Penelitian ini menggunakan pendekatan kualitatif metode deskriptif dengan mengambil lokasi di di Madrasah Tsanawiyah Muhammadiyah Fakfak dan Madrasah Tsanawiyah Negeri Fakfak. Hasil penelitian ini menunjukan bahwa (1) Pendekatan nilai Ketuhanan merupakan metode dalam membentuk karakter siswa, (2) Pengembangan nilai Ketuhanan selaras dengan sila pertama dalam Pancasila yaitu "Ketuhanan Yang Maha Esa", (3) Tenaga pengajar di lingkungan Madrasah Tsanawiyah yakin bahwa korupsi adalah merupakan tindakan yang melanggar nilai-nilai Agama, (4) Nilai yang dipahami siswa merupakan nilai Ketuhanan, (5) Siswa Madrasah Tsanawiyah sedikitnya sudah terbentuk karakter dengan ditanamkannya nilai-nilai Ketuhanan serta memahami mengenai nilai anti korupsi. Kata kunci: Pancasila, Nilai Ketuhanan, Pendidikan, Anti Korupsi.